MISKONSEPSI BAGI HASIL DARI USAHA TERNAK SAPI TERHADAP PRINSIP KEADILAN DALAM MUAMALAH - Farida Arianti; Pasli Yolanda; Zikra Rahmi (Jurnal AL-AHKAM, 2021)
The existence of livestock business practices carried out by the Dhamasraya community causes control over the profit sharing of the union assets. The purpose of this study is to correct public misunderstandings about the results obtained from joint efforts (mudharabah contracts). This type of research is archival research in Damasraya with a phenomenological approach. The technique used with snowball sampling  is  cattle  breeders  (herders)  and  cattle  owners.  The  method  used  is through direct interviews with herders and livestock owners. How to analyze this research with qualitative descriptive analysis. The results of the study found that the distribution of livestock products from the delivery of pregnant female cows and female cows to herders had led to economic control that led to a monopoly, because the results of the cattle business cooperation were union profits/profits that would be distributed in a balanced manner. Balanced is positioning the distribution of respective rights for the benefit of cooperation.